Does High Medial Elbow Stress During Pitching Compromise the Dynamic Stabilizers of The Elbow? - Malachy P. McHugh; Michael J. Mullaney (North American Sports Medicine Institute, 2023)
# Background The flexor carpi ulnaris (FCU) and flexor digitorum superficialis (FDS) are thought to provide dynamic stability to the medial elbow, with a lesser contribution from the pronator teres (PT). # Hypothesis/Purpose The purpose of this study was to determine if baseball pitchers with higher valgus elbow torque experience greater FCU and FDS strength loss. # Study Design Controlled Laboratory Study # Methods A pilot study was performed to determine if middle and ring finger flexion strength tests preferentially activated the FCU and FDS versus the PT (10 men age 36±12 yr). EMG amplitudes, expressed as percent of maximal voluntary contraction (MVC) were compared between tests and muscles. In a field study of college baseball pitchers, middle finger, ring finger and grip strength were tested prior to, immediately after, and one day after 14 pitching performances in 10 pitchers (21±2 yr). Elbow valgus torque was measured from an inertial measurement unit, housed in a compression sleeve and pitchers were categorized as having high or low valgus torque. # Results For the pilot study EMG activations were 74% FDS, 66% FCU and 35% PT for the middle finger test (muscle effect p=0.032) and 93% FCU, 61% FDS and 23% PT for the ring finger test (muscle effect p=0.005). In the field study, pitchers with high valgus torque showed marked post-game middle finger fatigue (88% of baseline) and incomplete recovery the following day (95%), while pitchers with low valgus torque showed no strength loss (107% post game, 106% a day later; group x time p=0.022). Results were similar for ring finger strength (high torque: 94% post game 96% a day later; low torque: 114% post game 107% a day later; group x time p=0.048). By contrast, grip strength was not different between pitchers with high versus low valgus torque (p=0.143). # Conclusion High medial elbow stress during pitching fatigues the dynamic stabilizers of the medial elbow. # Level of Evidence Level 3